A Comprehensive Systematic Review of Prevalence, Risk Factor, Diagnosis, Management and Interventions for Dry Eye Disease - Raenose (International Medical Journal Corp. Ltd, 2025)
Background: Dry Eye Disease (DED) is a prevalent and multifactorial ocular condition characterized by a deficiency in tear production or excessive tear evaporation, leading to ocular discomfort, visual disturbances, and potential damage to the ocular surface. This systematic review aims to comprehensively evaluate the current literature on the prevalence, risk factors, diagnosis, management, and interventions for DED. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2015 to 2025. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 2,172 articles were initially identified through online databases (PubMed, SagePub, SpringerLink, and Google Scholar). After three rounds of screening, eight relevant studies were selected for full-text analysis. Conclusion: DED is a complex and multifaceted condition influenced by numerous demographic, environmental, and iatrogenic factors. Advances in diagnostic technology and personalized treatment approaches hold promise for better disease management. Continued research and multidisciplinary collaboration are essential to developing more effective strategies for preventing and treating DED, ultimately improving patient outcomes and quality of life.